The practice of experimental investigations of lexical tones in Baltic subdialects: some of the new insights in methodology - Evaldas Švageris (Lietuvių Kalba, 2020)
This article provides an alternative way of experimental investigation of lexical tones in the Baltics. The main idea holds on a presupposition that the phonetic basis of prosodic elements in question can be explained in a more appropriate way in terms of a combined analysis of acoustic correlates, rather than a selective one. The lexical tone in this case may be interpreted as a factor which determines the type of acoustic correlation. Ideally, the interdependence of that sort could be defined by mathematical functions. The analysis of the empirical basis provides clear evidence in the favour of such methodological approach. Phonetic data from both, the Latvian (Valmiera) and the Lithuanian (North Žemaitian) subdialects confirmed clearly that the highest level of the tone distinction can be reached by a combined analysis of the pitch slope, pitch jerk and the duration of the long accented vowels. These results have arguably improved the interpretation of the phonetic tone structure and shed a new light on the typological links between the Baltic dialects. Finally, it presupposes that the phonetic nature of prosodic elements in some degree depends on a methodological way we choose for the investigational purposes.